Politische Mantik: die Kommunikation über Götterzeichen und Orakel im klassischen Griechenland - Trampedach, Kai (Studien zur Alten Geschichte, 2015)
An analysis of divine messages in ancient Greece: prophecies, oracles, and dreams that not only play a major role in Greek texts of all genres, but also influenced real political decisions. This book asks the questions: In what way did divine messages happen? How were they constructed? In which contexts did they become significant? Which groups or individuals could use divine messages, in which ways? Which social and political actions did divine messages cause? What political influence was given to the gods, and under what circumstances? The author approaches this topic from the perspective of cultural anthropology and seeks to compare the specific profile of Greek divine messages with other mantic systems. He first discusses mantic communication through signs and oracles (the most important forms and methods of divine messages). Then he examines divine messages in different political contexts, focusing on Athens, Sparta, and the panhellenic hegemony. Finally, he discusses the implicit theological assumptions, comparing them to alternative ethnographical ideas, philosophical concepts, and worldviews
Keywords: Hochschulschrift; Mantik; Politik; Griechenland; Geschichte 750 v. Chr.-323; Kommunikation